ANALYSIS OF RELIGIOUS SATIRE IN PBITEKS SONG OF LAWINO - Chris Ajibade Adetuyi; Patrick Charles Alex (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
This paper focuses on the analysis of religious satire in Song of Lawino. The study occasionally refers to Okots life history and ideological inclinations and the review of related literature giveng background information that clarifies Okot pBiteks writing as a product of a rich Acholi oral tradition. While a lot has been written on Okots creative works, little attention has been given to the use of satire. The study therefore, identifies and evaluates Okots use of satire in Song of Lawino determines the use of language to achieve satire in the text, and discusses how the author uses satire as a tool to share ideas and opinions on religious perspectives in the society. This study treats satire as the humorous criticism of human weaknesses and foibles and uses this parameter to identify it in the Song of Lawino. This is to throw light on the creative works of Okots and highlight circumstances that may have shaped him into a satirist. The upshot of all these is that the songs are appropriately contextualized with the ultimate finding that satire is an indigenous African phenomenon amply and ably deployed in Okots art.